2006
DOI: 10.1210/en.2005-0728
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone-Expressing Neurons Immortalized Conditionally Are Activated by Insulin: Implication of the Mitogen-Activated Protein Kinase Pathway

Abstract: Energy balance exerts a critical influence on reproduction via changes in the circulating levels of hormones such as insulin. This modulation of the neuroendocrine reproductive axis ultimately involves variations in the activity of hypothalamic neurons expressing GnRH. Here we studied the effects of insulin in primary hypothalamic cell cultures as well as a GnRH neuronal cell line that we generated by conditional immortalization of adult hypothalamic neurons. These cells, which represent the first successful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
3
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 59 publications
2
62
3
4
Order By: Relevance
“…The GnRH mRNA level peak after one hour of insulin treatment corresponds with the time of maximal Egr-1 protein levels, suggesting that higher protein levels, rather than protein activation, promote binding of Egr-1 to the GnRH promoter. In contrast to our findings, insulin increased Egr-1 mRNA levels to a lesser extent and increased GnRH mRNA levels two hours after insulin treatment in a model of conditionally immortalized and GnRH expressing rat hypothalamic neurons (Salvi et al, 2006). However, this study did not measure GnRH mRNA levels at one hour of treatment and 100 fold greater doses of insulin were used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The GnRH mRNA level peak after one hour of insulin treatment corresponds with the time of maximal Egr-1 protein levels, suggesting that higher protein levels, rather than protein activation, promote binding of Egr-1 to the GnRH promoter. In contrast to our findings, insulin increased Egr-1 mRNA levels to a lesser extent and increased GnRH mRNA levels two hours after insulin treatment in a model of conditionally immortalized and GnRH expressing rat hypothalamic neurons (Salvi et al, 2006). However, this study did not measure GnRH mRNA levels at one hour of treatment and 100 fold greater doses of insulin were used.…”
Section: Discussioncontrasting
confidence: 99%
“…Our laboratory recently demonstrated that insulin can increase GnRH gene expression in a GnRH-expressing neuronal cell line, suggesting that the observed phenotype in NIRKO mice may be due to insulin acting directly on the GnRH neuron (Kim et al, 2005). These observations were corroborated in a study using a model of conditionally immortalized GnRH-secreting neurons derived from rat hypothalamus (Salvi et al, 2006). In both studies, insulin stimulates a mitogen-activated protein (MAP) kinase pathway but the intermediary transcription factors important to transduce insulin's effects were not elucidated.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We have previously reported and confirmed again in this study that there is a highly significant inverse relationship between plasma testosterone and CRP concentrations (V.B., R.T., S.D., A. Chandel, A.C., H.G., P.D., unpublished observations). It has previously been shown that insulin may facilitate gonadotropin-releasing hormone release from hypothalamic neurons in vitro and that interference with insulin signal transduction may reduce gonadotropin-releasing hormone secretion (22). Because inflammatory mediators interfere with insulin signal transduction, they may contribute to the pathogenesis of hypogonadotrophic hypogonadism.…”
Section: Results -The Plasma Total Testosterone and Cft Concentrationmentioning
confidence: 99%
“…Moreover, our data shows that hypoleptinemia is a major contributing factor for the decreased KiSS-1 expression and hypogonadotropism of diabetic rats. That intracerebral administration of insulin failed to rescue KiSS-1 expression centrally does not preclude its potential modulatory action at other levels of the gonadotropic axis (e.g., on GnRH neurons) (42), but it strongly suggests that insulin per se is not sufficient to restore normal gonadotropic function in the face of persistently decreased KiSS-1 tone.…”
Section: Discussionmentioning
confidence: 99%